From S‐band mobile interactive multimedia to fixed satellite interactive multimedia: making satellite interactivity affordable at Ku‐band and Ka‐band. (3rd November 2015) - Arcidiacono, A.; Finocchiaro, D.; Collard, F.; Scalise, S.; Lazaro Blasco, F.; De Gaudenzi, R.; Cioni, S.; Alagha, N.; Andrenacci, M.
Summary: This paper describes the evolution of the ETSI S‐band mobile interactive multimedia protocol to support fixed satellite interactive multimedia (F‐SIM) services exploiting existing Ku‐band and Ka‐band satellites. The key F‐SIM protocol differences for both physical and upper layers are described and justified. The F‐SIM protocol has been adopted by the recently deployed Eutelsat Broadcast Interactive System whose architecture, key system parameters, link budget examples and key composing elements are also described. Finally, a summary of laboratory and field trials results over the Eutelsat KA‐SAT multibeam satellite are illustrated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The figure shows a typical user terminal implementing fixed interactive multimedia services (F‐SIM). The Smart low noise block (LNB) provides Internet protocol (IP) connectivity to the users' network. The user is able to get access to interactive multi‐media systems exploiting the F‐SIM protocols and a small dish. All radio frequency and baseband processing functions are integrated in the outdoor unit (ODU), which communicates with an indoor unit (IDU) via a normal coaxial cable.